Prescribing Information Therapy - Amy K. Chesser PhD; Nicole C. Keene Woods PhD (C); Aaron A. Davis DO; Caleb J. Bowers MD (SAGE Publishing, 2012)
Background : Recently, experts have included information therapy (Ix) as a method for increasing clinician-patient communication, patient adherence, patient understanding of diagnosis and treatment options, and reduction in hospitalizations. Methods : This study, a secondary, retrospective analysis of survey data, independently examined participating patient perceptions of an Ix program between two Mid-western employers. Surveys were administered through the online platform from January 1, 2006 through December 31, 2009 for Employer 1 (N = 4105) and from June 1, 2007 through December 31, 2009 for Employer 2 (N = 8123). Results : Preliminary findings indicate the majority of patients were adherent to recommended treatment(s) and highly rated their physician's performance. Additionally, patients indicated that their physician's access to their questionnaire responses motivated them to improve their health literacy and change their health behaviors. Secondary data analysis indicated a positive relationship between prescribed Ix and self-reported health literacy. Conclusion : As Web-based Ix increases in frequency, the evaluation of patient and clinician communication is important and should be expanded to increase the benefits for both patients and clinicians.